The Role of Oxybutynin Chloride in the Management of Patientswith Benign Prostatic Hyperplasia - N. Helal, Nehad; A. Salih, Rabei; M. Abdul-Azizr, Mohammed (Tikrit Journal of Pharmaceutical Sciences, 2023)
Objectives: To determine the efficacy and tolerability of Oxybutynin chloride in men with benign prostatic hyperplasia (BPH) and lower urinary tract symptoms (LUTS) in which previous a-blocker therapy had failed. : Materials and Methods: A total of 38 consecutive men with BPH complaining of LUTS in whom a mean of 6.3 months of a-blocker therapy had failed received Oxybutynin (5 mg twice daily orally) for 3 months in addition to the usual a-blocker medication. Primary efficacy end points were American Urological Association symptom score, and mean daytime and nighttime micturition frequency. Secondary end points were the peak urinary flow rate, post-void residual volume, the incidence of urinary retention, and adverse events. Statistical analysis was used when needed. Results: A total of 33 men (87%) with a mean age of 59 years completed the 3-month trial. Mean 24- hour micturition frequency decreased from 11.2 to 6.5 voids and nocturia decreased from 5.1 to 2.4 episodes nightly. Significant changes in mean American Urological Association symptom scores (- 5.31), the peak urinary flow rate (1.8 ml per second) and post-void residual volume (=21 ml) were also observed. Five men (13%) discontinued therapy because of intolerable dry mouth. There were no reports of urinary retention. Conclusions: Treatment with Oxybutynin in carefully selected men with BPH and moderate LUTS may be a reasonable therapeutic option after failed treatment with a-blockers.